The Second World War and the Protection of Saint George and the Dragon in Storkyrkan, Stockholm. (3rd July 2021) - Legnér, Mattias
Summary: When the Second World War broke out states, even neutral ones such as Sweden, sought to protect parts of their cultural property from destruction. This article deals with why and how some treasures belonging to the Church of Sweden were identified and selected for protection against air raids in the Second World War. On his own suggestion the art historian Johnny Roosval was given the task by the National Heritage Board ( Riksantikvarieämbetet ) to coordinate protective measures on churches by giving advice to dioceses and parishes. Soon he also became attached to the military headquarters, which made it possible for him to provide the armed forces with information about cultural property to be protected, and to forward requests for assistance. Measures taken in Storkyrkan in Stockholm following Roosval's initiative are studied. The evacuation of the fifteenth-century sculpture Saint George and the Dragon was unique in the sense that the resources allocated did not match the protection of any other cultural object in Sweden during the war years or later. The actions taken reflect an authoritative view on cultural heritage shaped by ideas of national identity and Swedish culture. The sculpture, then, signified the association between ecclesiastical heritage and Swedish national identity that the National Heritage Board was making. From having been largely forgotten, Saint George and the Dragon became – at least in the eyes of Roosval and the National Heritage Board – a symbol of national unity and sovereignty threatened by the war in Europe.